Delayed Diagnosis and Treatment of Traumatic Testicular Dislocation: A Case Report and Literature Review - Wang, Qihua; Alshayyah, Rami W. A.; Lv, Hang; Yu, Yang; Liu, Xinyu; Yang, Bo (Frontiers in Surgery, 2021)
Traumatic testicular dislocation is a rare complication secondary to different kinds of accident. A 61-year-old man came to urologic department to seek urethral reconstruction, who was injured by wall collapse and was diagnosed as pelvic fracture and posterior urethral rupture 5 months ago. However, thoroughly physical examination and imaging examination confirmed a round mass in right inguinal region and an empty right scrotum, which support diagnosis of testicular dislocation. The patient did not take the initiative to complain about that because he thought the right testis had been destroyed by the accident already. So patient underwent fiber cystourethroscopy, urethral reconstruction and orchiopexy. No testicular atrophy was confirmed at follow-up. We reviewed previous reports about traumatic testicular dislocation and analyzed the cause of delayed diagnosis.